2012
DOI: 10.1111/gcbb.12006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cross host species inoculation of nitrogen‐fixing endophytes on growth and leaf physiology of maize

Abstract: Plants that grow and thrive under abiotic stress often do so with the help of endophytic microorganisms. Although nitrogen-fixing (diazotrophic) endophytes colonize many wild plants, these natural relationships may be disrupted in cultivated crop species where breeding and genotype selection often occur under conditions of intensive fertilization and irrigation. Many energy crops including corn may still benefit from diazotrophic endophyte inoculations allowing for more efficient biomass production with less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
4
49
0
1
Order By: Relevance
“…These endophytes either as single strain or multi-strain inoculum have previously exhibited mutualistic behavior when added to other plant species including grasses, corn, rice, Douglas-fir and a variety of crop plants (Xin et al, 2009;Knoth et al, 2013;Knoth et al, 2014;Khan et al, 2012;Khan et al, 2015;DaSilveria et al, 2016). Combined application of endophytes can result in larger effects than those possible with individual inoculations (Knoth et al, 2013;Knoth et al, 2014;Rogers et al, 2012). In this study, the bacterial and fungal strains of different endophytes (Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…These endophytes either as single strain or multi-strain inoculum have previously exhibited mutualistic behavior when added to other plant species including grasses, corn, rice, Douglas-fir and a variety of crop plants (Xin et al, 2009;Knoth et al, 2013;Knoth et al, 2014;Khan et al, 2012;Khan et al, 2015;DaSilveria et al, 2016). Combined application of endophytes can result in larger effects than those possible with individual inoculations (Knoth et al, 2013;Knoth et al, 2014;Rogers et al, 2012). In this study, the bacterial and fungal strains of different endophytes (Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In this preliminary study, we chose a consortia of diazotrophic endophytes, originally isolated from poplar and willow trees [20][21][22], because they had shown robust growth-promoting activity with agricultural crops, grasses and poplar plants grown under abiotic stress [22,[39][40][41]. Our objective was to determine if these endophytes enhance the growth of Douglas-fir seedlings under nutrient-poor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2 . This difference may be due to very different environmental conditions, even if they are desert plants 11,17 . In our study, the abundance of endophytes decreased with soil alkalinity in site 20 where pH was 9.19 and had the lowest population density (Table 1).…”
mentioning
confidence: 99%
“…However, bacteria yielding the maximum number of mechanisms to promote plant growth were collected at the sampling sites where soil pH was both more acid (6.18) and alkaline (9.19) ( Table 1), which could be related to the production of root exudates acting as chemical signals to attract endophytic bacteria. It has been reported that there is increased production of root exudates when soil pH is acidic (pH 6) or alkaline (pH 8) 17 . Only eight representative isolates were chosen for having multiple plant-growth promoting properties for further analysis.…”
mentioning
confidence: 99%